False-negative testing for severe acute respiratory syndrome coronavirus 2: consideration in obstetrical care - Kelly, Jeannie C. (Am J Obstet Gynecol MFM, 2020)
Because the obstetrical population seems to have a high proportion of asymptomatic patients who are carriers of severe acute respiratory syndrome coronavirus 2, universal testing has been proposed as a strategy to risk-stratify all obstetrical admissions and guide infection prevention protocols. Here, we describe a case of a critically ill obstetrical patient with all the clinical symptoms of coronavirus disease 2019 and 3 false-negative results of nasopharyngeal swabs for molecular testing. We review and discuss the uncertain clinical characteristics of current severe acute respiratory syndrome coronavirus 2 molecular testing and the implications of false-negative results in the obstetrical population.